Optimasi Perencanaan Operasi Pembangkit Listrik Berbasis Mixed Integer Linear Programming (MILP) Pada Sistem Isolated Selayar - Agung Wicaksono; Rony Seto Wibowo; I Made Yulistya Negara (INTECOMS: Journal of Information Technology and Computer Science, 2024)
This study explores the integration of fossil and renewable energy generators on Selayar Island, focusing on optimizing Diesel Power Plants (PLTD) and Solar Power Plants (PLTS). Using Mixed-Integer Linear Programming (MILP) for generator scheduling, simulations reveal that a 15% rotational backup constraint positively impacts operational costs and system reliability. The findings provide practical recommendations for operators to enhance efficiency, reduce costs, and improve overall system reliability in the context of hybrid energy systems.